Prevalence, Causes, and Risk Factors of Presenting Visual Impairment and Presenting Blindness in Adults Presenting to an Examination Center in Suzhou, China - Ruizhu Sun; Dan Huang; Zhenxing Liu; Tingting Zhu; Zheyao Gu; Ge Ma; Yun Wang; Chunyuan Zhang; Xiangying Luo; Zhigang Tang; Ting Xi; Fangfei Xie (Journal of Ophthalmology)
Purpose. To evaluate the prevalence, causes, and risk factors of presenting visual impairment (PVI) and presenting blindness among adults in Suzhou, China. Methods. A total of 43927 subjects were included in this cross-sectional study. Each subject underwent ophthalmic examinations, including presenting visual acuity (PVA), intraocular pressure (IOP), slit-lamp examination, and fundus examination under the small pupils of each eye. Results. Using the World Health Organization (WHO) definition, the prevalence of bilateral PVI, bilateral presenting blindness, monocular PVI, and monocular presenting blindness was 1.59% (95% CI, 1.51–1.67), 0.002% (95% CI, 0.0019–0.0021), 3.87% (95% CI, 3.68–4.06), and 0.19% (95% CI, 0.18–0.20), respectively. Using the United States (US) definition, the prevalence of bilateral PVI, bilateral presenting blindness, monocular PVI, and monocular presenting blindness was 5.83% (95% CI, 5.54–6.12), 0.04% (95% CI, 0.038–0.042), 7.43% (95% CI, 7.06–7.80), and 0.45% (95% CI, 0.43–0.47), respectively. The prevalence of PVI was higher in females (WHO criteria, 2.06%, 95% CI, 1.96–2.16; US criteria, 7.27%, 95% CI, 6.91–7.63) than in males (WHO criteria, 1.2%, 95 CI%, 1.14–1.26; US criteria, 4.65%, 95% CI, 4.42–4.89). The leading cause of PVI is an uncorrected refractive error, followed by cataracts and age-related macular degeneration (AMD). Multivariate analysis proved that the prevalence of visual impairment (PVA, better eye, WHO criteria) increased significantly with older age, higher mean arterial pressure (MAP), higher globulin level, and higher fasting blood glucose (FBG). In addition, it also increased significantly with lower hemoglobin, a lower body mass index (BMI), and a lower arterial stiffness index. In this study, serum creatinine, blood urea nitrogen, uric acid, triglycerides, and the systemic immune-inflammation index (SII) showed no association with visual impairment. Conclusion. The leading causes of PVI in Suzhou were uncorrected refractive error and cataracts. The prevalence of PVI increased with females, older age, higher MAP, higher FBG, higher globulin, lower hemoglobin, lower BMI, and lower arterial stiffness index.